Environmental Sustainability Report 2022 / Ts. Dr. Nurzawani Md Sofian ... [et al.] - Md Sofwan, Nurzawani; Budin, Hemyza; Abd Rashid, Ahmad Faiz; Mohd Anas Khan, Mohd Yazid; Yusuf, Nur Afisha; Abu Bakar, Nur Ain; Wahed, Wan Juliana Emeih; Bohari, Asmah Alia; Morni, Affidah; Johari, Aiza; Perreau, Madeleine Edna (Perpustakaan Tun Abdul Razak, 2023)
This is the first environmental sustainability report for Universiti Teknologi MARA Sarawak branch. The report documents and highlights key sustainable initiatives in line with Sustainable Development Goals (SDGs) 2030 through its UiTM Sarawak Green Centre (UGC) and Sustainable Campus Committee. UiTM Sarawak Branch has taken great initiatives and placed its huge commitment in creating environmental awareness among its staff by conducting a comprehensive study in all three (3) campuses. All relevant documents gathered from the various faculties, divisions, centres and units were examined, analysed and compiled to provide accurate information and strong evidences for the report. Five (5) primary areas featured in the report which are aligned to the Environmental Management Systems (EMS), as presented in the MS ISO 14001, are Commitment and Policy, Planning, Implementing the Environmental Management Plan, Measurements and Evaluation, and Review and Improvement. The first area on Commitment and Policy, focuses on commitment by UiTM Sarawak Branch in practising and establishing the Environmental Policy, emphasising on the need for continuous effort to uphold duties and responsibilities towards protecting and preserving the environment. The second area, Planning, presents the plan to fulfil the environmental obligations declared in the Environmental Policy, by considering the environmental aspects, legal and other requirements, and environmental management programmes. The third area focuses on implementing the Environmental Management Plan (EMP). This area reports on the implementation of the environmental programmes held by UiTM Sarawak Branch in protecting and preserving the environment for the present and future generations. The Measurements and Evaluation is an area that explains the monitoring processes of the project and measures the effectiveness of the programmes. Finally, the area on Review and Improvement, describes the continuous improvement put forward while ensuring UiTM Sarawak Branch is moving towards more sustainable environmental management. It is hoped that from the documentation and evidences presented in the report, it will help reveal the seriousness and commitment of UiTM Sarawak Branch in the essence of environmental stewardship.